2008
DOI: 10.1371/journal.pone.0003063
|View full text |Cite|
|
Sign up to set email alerts
|

The Critical Role of Partially Exposed N-Terminal Valine Residue in Stabilizing GH10 Xylanase from Bacillus sp.NG-27 under Poly-Extreme Conditions

Abstract: BackgroundUnderstanding the mechanisms that govern protein stability under poly-extreme conditions continues to be a major challenge. Xylanase (BSX) from Bacillus sp. NG-27, which has a TIM-barrel structure, shows optimum activity at high temperature and alkaline pH, and is resistant to denaturation by SDS and degradation by proteinase K. A comparative circular dichroism analysis was performed on native BSX and a recombinant BSX (R-BSX) with just one additional methionine resulting from the start codon. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…RBSX and its mutants were found to unfold in an irreversible manner, and the apparent melting temperature ( T m ) was calculated for all protein samples with a constant temperature slope of 60 °C·h −1 . It was observed that the V1G and V1A mutations decreased the stability of the protein by 12 °C and 2 °C, respectively, whereas the V1F and V1D mutations did not significantly change its thermostability, as compared with RBSX . On the other hand, the V1L mutation markedly enhanced the thermostability of RBSX from 70 °C to 75 °C without compromising its catalytic activity, and resulted in higher cooperativity in the thermal unfolding transition .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…RBSX and its mutants were found to unfold in an irreversible manner, and the apparent melting temperature ( T m ) was calculated for all protein samples with a constant temperature slope of 60 °C·h −1 . It was observed that the V1G and V1A mutations decreased the stability of the protein by 12 °C and 2 °C, respectively, whereas the V1F and V1D mutations did not significantly change its thermostability, as compared with RBSX . On the other hand, the V1L mutation markedly enhanced the thermostability of RBSX from 70 °C to 75 °C without compromising its catalytic activity, and resulted in higher cooperativity in the thermal unfolding transition .…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study from our group, different extreme N‐terminus mutants of RBSX were generated in which the first residue, Val1, was replaced with various amino acids, and each mutant was subsequently analyzed for its thermal stability at high temperatures. The thermal stabilities of RBSX and the mutant proteins were determined by CD measurements at a range of temperatures . RBSX and its mutants were found to unfold in an irreversible manner, and the apparent melting temperature ( T m ) was calculated for all protein samples with a constant temperature slope of 60 °C·h −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations